How Students’ Social Emotional Skills Students were Developed through Innovative Emergency Remote Teaching of Performance-Based Courses during the Pandemic: Qualitative Study Using Participatory and Appreciative Action and Reflection Approach - Eunice M. Aclan; Nole Redentor Aclan; Jonalyn Aclon; Sheryl Ann de Dios; Khristine Ruth De Gracia; Nerilyn Beratio; Jewel Solidum; Warlito Yalung; Mary Ann Asi, (Journal of Communication in Scientific Inquiry (JCSI), 2024)
While the Covid-19 pandemic has mostly negative impacts causing millions of deaths and disrupted global economy, it nevertheless has some positive impacts particularly in higher education which shifted to emergency remote teaching [ERT]. Using Participatory and Appreciative Action and Reflection [PAAR] approach, this qualitative study explored strategies innovated by performance-based teachers for abrupt shift from face-to- face [FTF] to virtual ERT during the pandemic, how these innovative ERT strategies developed students’ social emotional skills [SELs], and what new insights they generated. Data were gathered through one-on-one interviews from five faculty members teaching Music and Physical Education [PE], both performance-based not easy to teach online. The interview data were transcribed, analyzed thematically, and triangulated with class observations, videos, and students’ reflections. Also, the perspectives of the teachers were triangulated with interviews from five Music and PE students. Results show that students developed creativity and resourcefulness, persistence, and engaging with others. The participants reflected that educators need not panic even in most adverse situations like the unexpected pandemic as they themselves have become more creative and resourceful to quickly shift to ERT and respond to students’ needs and more flexible to cater to students in different time zones with various challenges.